Analysis Of Financial And Non-Financial Performance Of The 3 Largest Companies In The United Kingdom’s Apparel Retail Industry For 2018-2022 - Sesa, Patricia Gloria Evania; Hasnawati, Hasnawati (International Journal Labs, 2023)
This study aims to analysis of the financial and non-financial performance of the 3 largest companies in the united kingdom's apparel retail industry for 2018-2022. This research use a quantitative with Cluster Random Sampling. Data was collected using documentation from companies annual report and sustainability report. The data were processed using financial ratios, ESG (Environmental, Sosial, and Governance) Score, PESTLE analysis, and Critical Success Factors. The results of this study show that the financial and non-financial performance of retail companies in England in 2018-2022 faced several factors that made these companies have to adapt starting from Pandemic Covid-19, brexit, shifts in consumer tastes, e-commerce developments, customers who are more concerned about environmental impacts, supply chain disruptions, and decreased consumer spending. The results of a comparison of financial and non-financial performance before the Covid-19 pandemic, and during Covid-19 for companies in the apparel retail sector in England in 2018-2022. Before Covid-19 companies had steady growth, reliance on physical stores, table supply chains, Employee well-being, and sustainability initiatives. During Covid-19 companies had different challenges such as Revenue decrease, E-commerce surge, and supply chain disruptions, financial strain, Digital transformation, and employee safety. As a whole, the Covid-19 pandemic forced companies in the clothing retail sector to change quickly and change their strategy in order to stay in business. This crisis shows how important it is to be flexible, digitally ready, and have a strong supply chain. Companies that have invested in digital capabilities and embraced e-commerce are better able to weather the storm. Sustainability and ethical practices remain important, but staying afloat and making changes to operations becomes even more important during the peak of the pandemic. The results also show that between the three companies Next plc has had a stable financial condition for the past five years, which is crucial for long-term success and growth in the retail industry. Next has also built a strong brand identity over the years. This recognition helps in building trust and attracting new customers, making it easier to introduce new products or expand into new markets.